Transitioning from public figures to entrepreneur: Analyzing the impact of influencer credibility on eliciting consumer purchase intention - Rani, Rani; Daulay, Muhammad Yasser Iqbal (Gema Wiralodra, 2024)
Influencer endorsements are one of the most popular marketing communications tools used by cosmetic products to shape consumer behavior. This study aims to analyze the effect of social media influencers' endorsement on consumer behavior in purchasing cosmetic products and explore the attributes of influencers who significantly impact this behavior. This research design uses a quantitative descriptive approach, which focuses on measuring variables to find patterns, relationships, and generalizations that can be applied to a wider population. Data analysis in this study used the SEM model with the help of SmartPLS 4.0 software. The research sample consisted of 128 people, with respondents categorized as having used mother-of-pearl products in Bengkulu City. According to the research findings, only 122 individuals were deemed eligible to be included as respondents. The research was conducted in November 2023. The research results show that an influencer's expertise, attractiveness, and suitability can increase their credibility. In contrast, an influencer's credibility can influence a person's intention to purchase cosmetic products. This is evidenced by a t-statistic value exceeding 1.96 and a p-value below 0.05. Meanwhile, the trust variable has an insignificant effect on credibility and purchase intention if mediated by credibility. This is evidenced by a T-statistic value below 1.96 and a p-value over 0.05. All hypotheses in this study can be declared accepted except hypothesis 1 and hypothesis 6a.